(untitled) (Journal of human and social sciences, 2024)
This paper addresses the emotional impact of the Hajj ritual in the works of Libyan poets. Before delving into the poets and their output, the study discusses the history of the modern poetic movement in Libya and its three stages of development: the Turkish era, the Italian era, and the Liberation era. Subsequently, the study focuses on six poets from different periods who, in their published and manuscript divans (poetry collections), reflected on the inspirations of Hajj, expressing their longing and nostalgia, and describing the feelings and rites of Hajj. The paper concludes with findings and recommendations.